2016
DOI: 10.1002/maco.201609158
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term spinodal decomposition – its effects on corrosion behaviour of a duplex stainless steel and feasibility as a strengthening treatment

Abstract: The present paper looks into the effects of spinodal decomposition (SD) on the corrosion resistance and cavitation erosion behaviour of the duplex stainless steel (DSS) 7MoPLUS. SD takes place at 500 8C in the ferrite phase at the early stage of thermal ageing, with an attendant hardness increase. Nevertheless, thermal ageing at this temperature for up to 2 days nearly does not reduce pitting potential (in 3.5% NaCl). Surface integrity, however, is degraded by the appearance of noticeable pits after just a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Similar tendencies were also found for Grade 600‐3 SG iron, for which the cavitation erosion rate can be reduced by a factor of six after being treated by laser treatment . A moderate CER enhancement of duplex stainless steel 7MoPLUS was reported as a result of spinodal decomposition at 500 °C for 5 h . Previous studies also showed that the change of CER depends on the temperature employed in the heat treatment.…”
Section: Introductionsupporting
confidence: 75%
“…Similar tendencies were also found for Grade 600‐3 SG iron, for which the cavitation erosion rate can be reduced by a factor of six after being treated by laser treatment . A moderate CER enhancement of duplex stainless steel 7MoPLUS was reported as a result of spinodal decomposition at 500 °C for 5 h . Previous studies also showed that the change of CER depends on the temperature employed in the heat treatment.…”
Section: Introductionsupporting
confidence: 75%
“…The G phase is usually very small in size, which is shown in Figure 6 for a duplex Figure 5. The ferrite and austenite of a grade 2205 duplex stainless steel after spinodal decomposition treatment [25].…”
Section: Spinodal Decompositionmentioning
confidence: 99%